Labor reallocation over the business cycle: New evidence from internal migration - Raven E. Saks; Abigail Wozniak (Institute for the Study of Labor (IZA), 2007)
This paper establishes the cyclical properties of a novel measure of worker reallocation: long-distance migration rates within the US. This internal migration offers a bird's eye view of worker reallocation in the economy as long-distance migrants often change jobs or employment status, altering the spatial allocation of labor. Using historical reports of the Current Population Survey (CPS), we examine gross migration patterns during the entire postwar era, a period that spans ten recessions over more than fifty years. We obtain additional evidence on inter-state and inter-metropolitan population flows during the past thirty years from statistics compiled by the Internal Revenue Service. We find that internal migration within the US is strongly procyclical in both sources. Even after accounting for variation in relative local economic conditions, migration is lower during downturns in the national economy. Using individual-level CPS data, we find that migration is procyclical for most major demographic and labor force groups, although it is strongest for younger workers. Our findings suggest that cyclical fluctuations in internal migration are driven by economy-wide changes in the net cost to worker reallocation with a major role for the job finding rate of young workers.
urn:nbn:de:101:1-2008040283
Keywords: 330; Arbeitsmobilität; Regionale Arbeitsmobilität; Binnenwanderung; Konjunktur; USA